Ragone Relations for Thermal Energy Storage Technologies - Yazawa, Kazuaki; Shamberger, Patrick J.; Fisher, Timothy S. (Frontiers in Mechanical Engineering, 2019)
The Ragone relation is a facile approach to assess and compare electro-chemical battery performance in terms of two critical performance parameters: power density and energy density. This power and energy nexus is equally relevant for thermal energy storage materials for thermal management applications that require a balance between energy storage capacity and on-demand cooling or heating rates. Here, thermal energy storage is evaluated for sensible heating and for phase-change materials (PCMs). We propose an analytic expression using a lumped mass model for thermal storage through an analogy with heat diffusion that allows for intuitive mapping of materials and components in power-energy space. In addition, a previously proposed figure-of-merit, η_q, describing the intrinsic capability of PCMs to rapidly absorb or discharge heat is placed in the context of the thermal Ragone (power-energy) relation. This figure of merit serves as a proxy for the cooling power of PCMs and single-phase materials to store thermal energy. Thus, η_q plotted against energy density can serve graphically to illustrate performance tradeoffs between different thermal storage materials, as well as composites composed of different materials.